POTENSI BAKTERI Pseudomonas sp. DAN Ochrobactrum sp. YANG DI ISOLASI DARI BERBAGAI SAMPEL TANAH DALAM MENDEGRADASI LIMBAH POLIMER PLASTIK BERBAHAN DASAR HIGH DENSITY POLYETHYLENE (HDPE) DAN LOW DENSITY POLYETHYLENE (LDPE) - Inas Riandi, Muhammad; Kawuri, Retno; Sudirga, Sang Ketut (SIMBIOSIS, 2017)
plastics on a large scale has an effect on the increase to the amount of world waste, such as High Density Polyethylene (HDPE) and Low Density Polyethylene (LDPE) plastics. This study, tried to isolate Pseudomonas and Ochrobactrum bacteria from various soil in dumped soil area and mangrove forest in Bali to find out the degradation ability of the bacteria against HDPE and LDPE plastics. The methods used in this study were pour plate method, Biochemical and morphology identification by using Bergey’s Manual of Determinative Bacteriology 9th Edition book as a reference, screening test and the determination of bacterial species by using Vitek 2 Compact System. Evaluation of degradation result was done by measuring the weight loss of plastics residues. This study has isolated 27 bacteria that estimated from genus Pseudomonas and Ochrobactrum with characteristics as basil shape, Gram negative, positive catalase and classified as non-fermenter bacteria. Isolate 2 bacteria which isolated from Suwung dumped soil has identified as Ochrobactrum anthropi with the ability of HDPE degradation by 20% and Isolate 24 which isolated from Karangasem dumped soil has identified as Pseudomonas aeruginosa with the ability of HDPE degradation by 18,75%. Keywords : Plastics waste, Biodegradation, High Density Polyethylene and Low Density Polyetene